Understanding Judaism - Yomtov, Nel (Understanding world religions and beliefs., 2019)
Describes the traditions, history, core beliefs, sacred scriptures, synagogues, and branches of Judaism. Also discusses the impact of Judaism on world civilization. Includes a facts section, color photographs, a glossary, and further resources.